2018
DOI: 10.1371/journal.pone.0198476
|View full text |Cite
|
Sign up to set email alerts
|

Computational quantum chemistry, molecular docking, and ADMET predictions of imidazole alkaloids of Pilocarpus microphyllus with schistosomicidal properties

Abstract: Schistosomiasis affects million people and its control is widely dependent on a single drug, praziquantel. Computational chemistry has led to the development of new tools that predict molecular properties related to pharmacological potential. We conducted a theoretical study of the imizadole alkaloids of Pilocarpus microphyllus (Rutaceae) with schistosomicidal properties. The molecules of epiisopiloturine, epiisopilosine, isopilosine, pilosine, and macaubine were evaluated using theory models (B3lyp/SDD, B3lyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 63 publications
1
18
0
4
Order By: Relevance
“…In this study, it is possible to detect the existence of four isomeric forms (C 16 H 18 N 2 O 3 ) for the alkaloids EPR ( Figure 1 a), EPS ( Figure 1 b), IPS ( Figure 1 c) and PS ( Figure 1 d). The presence of optical isomerism in the EPS, IPS and PS molecules is perceived, according to the results of Rocha et al [ 20 ], observed through the rotation of two conforming atoms (C4 and C9), and by the presence of three chiral carbons (C5, C7, and C8), which corroborate with the data presented in the experimental studies of Rocha et al [ 23 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, it is possible to detect the existence of four isomeric forms (C 16 H 18 N 2 O 3 ) for the alkaloids EPR ( Figure 1 a), EPS ( Figure 1 b), IPS ( Figure 1 c) and PS ( Figure 1 d). The presence of optical isomerism in the EPS, IPS and PS molecules is perceived, according to the results of Rocha et al [ 20 ], observed through the rotation of two conforming atoms (C4 and C9), and by the presence of three chiral carbons (C5, C7, and C8), which corroborate with the data presented in the experimental studies of Rocha et al [ 23 ].…”
Section: Resultssupporting
confidence: 89%
“…In order to obtain the global minimum energies, thermodynamic properties, Molecular Electrostatic Potential Surface (MEPS), frontier molecular orbitals and descriptors of the global chemical reactivity of the ligands, calculations geometric optimisation and frequency in the gas phase (vacuum system) were performed, at the level of Density Functional Theory (DFT) and based on studies by Rocha et al [ 20 ] and Costa et al [ 32 , 33 ]. For this purpose, it was used the Gaussian 09 software [ 34 ] and the B3LYP hybrid method [ 35 , 36 ] associated with the basis set 6-311++G(d,p) [ 37 , 38 ].…”
Section: Computational Detailsmentioning
confidence: 99%
“…Frequency calculations were performed to obtain thermodynamic properties and to verify that each optimization achieved an energy minimum. The quantum chemical descriptors extracted directly from the ORCA output le were Huckel charge, electronic density, dipole moment, the energy of the highest occupied molecular orbital (HOMO), and the energy of the lowest unoccupied molecular orbital (LUMO) [21,22].…”
Section: Computational Chemistrymentioning
confidence: 99%
“…Frequency calculations were performed to obtain thermodynamic properties and to verify that each optimization achieved an energy minimum. The quantum chemical descriptors extracted directly from the ORCA output le were total energy, Mulliken atomic charges, electronic density, dipole moment, Mayer population analysis, the energy of the highest occupied molecular orbital (HOMO), and the energy of the lowest unoccupied molecular orbital (LUMO) [15,16]. The molecular orbitals and the optimized structures taken by AVOGADRO software [17].…”
Section: Density Functional Theory Studiesmentioning
confidence: 99%